CALLA negative precursor B lymphoblastic leukemia with MLL gene translocation and an unusual FISH signal pattern - Sandhya G Devi; Manu Goyal; N. V. S. S. Ramakrishna; S Sudha Murthy (Wolters Kluwer Medknow Publications, 2011)
Rearrangements of the mixed lineage leukemia (MLL) gene at 11q23 commonly occur in infants with CALLA negative B lymphoblastic leukemia (B-ALL). Most often, these are detected by conventional karyotyping; however, fluorescent in-situ hybridization (FISH) with the help of a dual-color break-apart probe is used to identify cryptic translocations. When there is an MLL gene translocation, the usual FISH signal pattern is 1 red-1 green-1 yellow fusion signal pattern. We present a case of an infant with CALLA negative precursor B-ALL with a characteristic translocation t(4;11) (q21;q23), however, with an unusual MLL FISH signal pattern.